Pengaruh suplementasi Fe dan Zn terhadap kadar hemoglobin dan kesegaran jasmani pada lansia anemia di Kabupaten Bantul - Endang Pamungkasiwi; Wiryatun Lestariana; Retno Pangastuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: Province of Yogyakarta Special Territory is a province of “elderly” structure population, as viewed from the number of elderly which is 15% of total population. Anemia is one of nutrition problems of elderly which reaches as high as 50%. This is caused by low intake of iron and other substances related to iron metabolism process in forming hemoglobin. Low hemoglobin concentration can be one of causes of elderly declining physical fitness. Efforts to overcome anemic problems can be done through the supply of iron and zinc for the elderly twice a week.Objective: To know effect of iron and zinc supply to hemoglobin concentration and physical fitness for anemic elderly at Bantul District, Province of Yogyakarta Special Territory.Methods: The study was a randomized double blind controlled trial design. Subject of the study were anemic elderly that fulfilled inclusion criteria. The supply of iron, combination of iron and zinc to trial group was given twice a week on different days, supply of iron was given on Monday and Thursday, while supply of zinc was given on Tuesday and Saturday. Laboratory and physical fitness examination to both group were done prior and after treatment. Nutrition intake data were achieved through food record. Next, to know effect of iron, iron and zinc supply to elderly hemoglobin concentration and physical fitness, covariant analysis was done.Results: The result of the study showed that after 3 months’ treatment, there was significant difference of hemoglobin concentration caused by different treatment of group with iron supply, iron and zinc combination supply and control group (p=0.012) although iron and combined iron and zinc supply had equal effectiveness in increasing hemoglobin concentration (p=0.404). There was no significant relationship between elderly hemoglobin concentration and physical fitness (p=0.448). This showed that treatment given affected increase of hemoglobin concentration but the supply and increase of hemoglobin concentration did not affect increase of elderly physical fitness.Conclusion: The supply of iron and combined iron and zinc increase hemoglobin concentration, but the supply and in- crease of hemoglobin concentration did not increase the elderly physical fitness.